The Good, the Bad, and the Indifferent: Physical Disability, Social Role Configurations, and Changes in Loneliness Among Married and Unmarried Older Adults. (September 2019) - Warner, David F.; Adams, Scott A.; Anderson, Raeda K.
Objectives: To examine how social role configurations (SRCs)—combinations of the quality of spousal, family, and friend relationships—moderate the association between functional limitations (FLs) and loneliness among married and unmarried older adults and whether this differs by gender.Method: Longitudinal data from the National Social Life, Health, and Aging Project on married ( n = 945) and unmarried ( n = 443) older adults (aged 57-85 years). Latent class analysis was used to identify SRCs. Tobit regression models examined the associations between FLs, SRCs, and loneliness.Results: Nine SRCs were identified. The effectiveness of SRCs for coping with FLs did not differ by marital status despite higher loneliness among the unmarried. Only for women with FLs did SRCs characterized by negativity/strain exacerbate loneliness. For men with FLs, SRCs characterized by excess positivity/support were problematic.Discussion: These findings underscore the importance of considering how SRCs provide resources for coping with FLs that have gendered implications.